Peran Kontrol Diri terhadap Fear Of Missing Out Coffee Shop Viral di Media Sosial pada Remaja Akhir di Jakarta - Kartohadiprodjo, Aisha Pramadita; Suryadi, Denrich (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
The Fear of Missing Out (FoMO) Scale, developed by Przybylski, Muryama, DeHaan, and Gladwell (2013), and the self-control scale created by Averill (1973) were both used in this study. Correlation analysis results showed an r-value of -0.913 with Sig. (2-tailed) = 0.000 (p < 0.05), indicating a significant negative relationship between self-control and Fear of Missing Out (FoMO). Additionally, the study found that self-control contributed effectively by 33% to Fear of Missing Out (FoMO), while the remaining 67% was influenced by other factors outside the study. The purpose of this research was to determine the level of self-control exercised by late adolescents in Jakarta toward coffee shops that became popular on social media due to Fear of Missing Out (FoMO). The uncomfortable sensation of feeling left out of others' experiences or possessions is known as Fear of Missing Out (FoMO), which often prevents individuals from appreciating the present. Self-control, a crucial skill, allows individuals to adapt to their environment through appropriate behavior, understanding, and decision-making. Fear of Missing Out (FoMO) occurs more frequently in individuals with poor self-control as they struggle to resist impulses and minimize the impact of social media. A total of 403 late adolescents (aged 18–22) who frequently visited coffee shops at least once a week and were active on social media were selected as the study sample.